'What a troupe family does': Family as Transmission Narrative in the British Carnival Troupe Dancing Community. (May 2019) - Wright, Lucy
Abstract : Troupe dancing, also known as 'entertaining', is a competitive formational dance performed by girls and women in the North of England and Wales. Demanding significant discipline and commitment to achieve the high levels of synchronisation expected for a successful routine, participants demonstrate a strong sense of community, frequently describing their teammates in terms that connote a familial relationship. Drawing on recent fieldwork with members of entertaining troupes in Staffordshire and Greater Manchester, this article outlines some of the ways in which the 'troupe family' is invoked at troupe dancing events, including End of Season Championships and Family Night celebrations, as well as the crucial role played by troupe families in providing a shared context for rites of passage associated with the life cycle, such as births, deaths and marriages. I suggest that appeals to the troupe family reflect the high status placed on familial identities in the working-class communities of which troupe dancing is a part. Further, I argue that the family constitutes a transmission narrative in contradistinction to the use of 'tradition' in the cognate English folk dance community. This article considers the implications of the family model, and its affordances in safeguarding carnival performance while embracing change and renewal.